Kestabilan implan gigi 46 dengan diameter 3,3 mm - Magdalena Yuniati, Maria; Tjandrawinata, Rosalina (Fakultas Kedokteran Gigi Universitas Trisakti, 2023)
Background: Losing teeth can cause problems such as the emergence of mastication, aesthetics, and phonetics. One of the solutions to restore these functions is dental implant. This method is in demand because apart from being able to restore function, the implant will also protect the jawbone from the process of resorption due to tooth loss. This is possible because dental implants are surgically implanted into the jawbone, then dentures can be placed over them to adapt the oral condition Case report: A 63-year-old woman with controlled hypertension came with complain of extracted lower right tooth 1 year ago and she wanted a fixed prosthesis to replace this tooth. She had not good experience with removeable denture at upper jaw. the jawbone has undergone resorption due to tooth loss which was not immediately rehabilitated. A single unit Straumann BLT dental implant of diameter 3.3 mm x height 10 mm is placed on this patient after treatment planning with radiograph image and study model analysis. Screw-cemented retained prosthesis was delivered on the implant to restore the function and aesthetic of the missing 46 tooth. Conclusion: Good planning and proper procedure during implant placement and restoration will lead to an excellent long-term aesthetic and functional outcome.